SIFAT MEKANIS KOMPOSIT MATRIKS ALUMINIUM BERPENGUAT ABU JERAMI DENGAN METODE METALURGI SERBUK - A A ALIT TRIADI; S SUGIMAN; L.R. KALBI (GANEC SWARA, 2024)
The powder metallurgy method is one method for making metal matrix composite products. This method provides researchers with material engineering.This study aims to determine how the effect of variations in mixing time and sintering holding time affects the hardness and compressive strength of composites made of aluminum powder and straw ash. The composition of this composite is 90%wt Aluminum and 10%wt straw ash. Preparation of specimens using powder metallurgy method. Mixing time variations were applied for 120, 150 and 180 minutes with the dry mixing method. Variation of sintering holding time was applied for 60, 120 and 180 minutes at 550°C.The mechanical test carried out are hardness test and compression test. The results showed that the optimum hardness value was found in the specimens with a mixing time of 150 minutes and sintering holding time of 180 minutes with an average hardness of 96 HRF. The optimum compressive strength is found in specimens with a mixing time of 150 minutes and sintering holding time of 120 minutes with an average compressive strength of 101.28 MPa. It can be concluded that mixing time and sintering holding time affect the hardness and compressive strength of the metal matrix composite.